Lymphaticovenular Anastomosis in Breast Cancer Treatment-Related Lymphedema: A Short-Term Clinicopathological Analysis from Indonesia - Brahma, Bayu; Putri, Rizky Ifandriani; Reuwpassa, Jauhari Oka; Tuti, Yustia; Alifian, Muhammad Farid; Sofyan, Rian Fabian; Iskandar, Iskandar; Yamamoto, Takumi (Journal of Reconstructive Microsurgery, 2021)
Background Locally advanced breast cancer is commonly found in Indonesia. In this group of patients, aggressive treatment such as axillary lymph nodes dissection (ALND) with or without regional nodal irradiation (RNI) will increase the risk of breast cancer treatment-related lymphedema (BCRL) in our patients. Lymphaticovenular anastomosis (LVA) has been established as a minimally invasive approach in lymphedema surgery. In this study, we report our first experience of LVAs in BCRL patients.Methods This was a cross-sectional study taken from breast cancer patients receiving ALND with or without RNI. From December 2018 until June 2020, we collected and described general patient information, tumor characteristics, diagnostic methods, and the outcome of LVA. Postoperative subjective symptoms scores (lymphedema quality-of-life score [LeQOLiS]) and lymphedematous volume (upper extremity lymphedema [UEL] index) were compared with preoperative ones.Results Seventy patients experienced BCRL with the mean age of 54.8 (9.4) years and mean body mass index of 28.1 (4.5). ALND was performed in 66 (97.1%) cases and RNI was given in 58 (82.9%) patients. Thirty-one (44.3%) patients were in the International Society of Lymphology stage 1, 24 (34.3%) in stage 2A, and 15 (21.4%) in stage 2B. The mean lymphatic vessel diameter was 0.5 (0.26) mm and 0.80 (0.54) mm for the vein. Lymphosclerosis severity was 7 (4%) in S0 type, 129 (74.1%) in S1 type, 37 (21.3%) in S2 type, and 1 (0.6%) in S3 type. In histopathology examination, S1 types were in lower grade injury, while S2 and S3 types were in the higher grade. Seven (53.8%) cases of S2 type showed severe fibrosis from trichrome staining. Postoperative LeQOLiSs were significantly lower than preoperative ones (5.6 ± 2.4 vs. 3.7 ± 2.6; p = 0.000). With the mean follow-up of 7.4 (3.7) months, the overall UEL index reduction was 9.2%; mean –11 (16.8). Postoperative UEL index was significantly lower than preoperative ones (117.7 ± 26.5 vs. 106.9 ± 18.5; p = 0.000). No complications were observed during this period.Conclusion LVA reduced the subjective symptoms and UEL index in BCRL cases. Future studies using updated imaging technologies of the lymphatic system and longer follow-up time are needed to confirm our results.
Keywords: lymphaticovenular anastomosis; breast cancer treatment-related lymphedema; axillary lymph nodes dissection